Memenangkan Suara Generasi Z: Strategi Dempo Xler di Pemilu 2024 - Silvia Amanda Putri; Lisa Adhrianti; Neneng Cucu Marlina (Mahesa Research Center, 2023)
Currently, technology is being used in political campaigns on social media. The 2024 Legislative Election has provided the latest color in the current campaign situation, this was also carried out by one of the legislative candidates from Bengkulu City, Dempo Xler. Generation Z had a big impact on the 2024 elections. This study aims to find out how Dempo Xler's social media political strategy is to win the Z generic vote in the 2024 election. This study used a descriptive qualitative method. This study uses interviews and observations as research instruments. The results showed the strategy carried out by Dempo Xler in gaining Gen Z votes by forming personal branding and conducting persuasive communication. The strategy has a positive impact and response from Gen Z in Bengkulu City, both support, suggestions, and constructive criticism so that later this can help in achieving goals in the 2024 election. This research concludes that Dempo Xler makes social media in line with the correlation of personal branding and persuasive communication as a form of perfection in political campaign strategies to get Generation Z votes in the 2024 election.